(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In every science, it is important to provide the conditions for the professional growth, self-development and self-realization of the specialist in the given field. The study of those conditions, the objective and subjective factors contributing to or hindering them was also the basis for the formation and development of the new science. Acmeology is the science that studies the personal and professional growth of a specialist, the gradual development and improvement of his professionogram and psychogram. At the core of the study of acmeology is not only individual, but also professional development of a person, so it has common appeals with Pedagogy science, because the development of professional knowledge, abilities and skills of educators ensures the further development and advancement of the field of education. This article aims to study the approaches of Pedagogical Acmeology in the professional development of the pedagogue of the 21st century.